Increasing access to care for young adults with cancer: Results of a quality-improvement project using a novel telemedicine approach to supportive group psychotherapy*. Issue 2 (26th July 2016) - Melton, Laura; Brewer, Benjamin; Kolva, Elissa; Joshi, Tanisha; Bunch, Michelle
Abstract: Objective: Young adults with cancer experience high levels of psychological distress. Group interventions for cancer patients have been effective in reducing levels of psychological distress but suffer from high levels of attrition and serve a limited geographic area. In a quality-improvement project, we converted an existing in-person support group to a telemedicine format in the hopes of improving attendance and reducing geographic disparities in access to care. Method: Eight young adults (18–40 years) with cancer were recruited from across Colorado. Participants received a tablet equipped with Wi-Fi and downloaded an HIPAA-compliant video-conferencing application. Participants attended six weekly supportive psychotherapy sessions. Results: Participants found the group to be beneficial: the technology worked, they enjoyed the group format, and they would recommend it to others. The novel treatment interface allowed for low attrition rates due to the flexibility of a patient's location during the intervention. It allowed for provision of services to a geographically diverse population of medically ill young adults, as participants lived an average of 148 miles from the cancer center (range = 25–406 miles). Significance of results: Internet-based mental health care is an area of growing interest for providers, but few studies have evaluated its efficacy in patients with cancer, and even fewer in young adults with cancer. Incorporating technological advances into clinical practice will increase access to care, reduce geographic health disparities, and provide more consistent services.